2021
DOI: 10.1051/0004-6361/202141809
|View full text |Cite
|
Sign up to set email alerts
|

Search for pairs and groups in the 2006 Geminid meteor shower

Abstract: Context. The existence of pairs and groups of meteors during meteor showers has been an open question for a long time. The double-station video observation of the 2006 Geminid meteor shower, one of the most active annual showers, is used for the search of such events. Aims. The goal of the paper is to determine whether the observed pairs of Geminid meteors are real events or cases of random coincidence. Methods. The atmospheric trajectories of the observed meteors, photometric masses, and both time and spatial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…As the number of meteors observed in a short time interval increases, the likelihood of the presence of a cluster increases. The search for meteor pairs and groups among the Geminid meteors found no evidence for their existence within this meteor shower (Koten et al 2021). If the cluster is observed during activity of a weak meteor shower or if the meteors are sporadic, the probability of a real connection between the meteoroids increases anew.…”
Section: Introductionmentioning
confidence: 94%
“…As the number of meteors observed in a short time interval increases, the likelihood of the presence of a cluster increases. The search for meteor pairs and groups among the Geminid meteors found no evidence for their existence within this meteor shower (Koten et al 2021). If the cluster is observed during activity of a weak meteor shower or if the meteors are sporadic, the probability of a real connection between the meteoroids increases anew.…”
Section: Introductionmentioning
confidence: 94%
“…However, the question is whether these meteoroids are actually physically related. Similarly, Koten et al (2021) observed three Geminid meteors within 0.9 s and they cannot rule out the possibility that the triplet is only a result of chance. Piers & Hawkes (1993) observed five meteors in a fraction of a second over Canada in 1985.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the frequency of meteoroid self-fragmentation in space has implications for our current understanding of the Solar System. Since Koten et al (2017), only one meteor cluster observation has been reported (University of Hawaii 2021), although an extensive search was recently performed among the Geminids (Koten et al 2021). One open question refers to the frequency of spontaneous meteoroid breakup in interplanetary space, which would lead to meteor clusters and how these breakups would influence the lifetime expectancy of meteoroids.…”
Section: Introductionmentioning
confidence: 99%